2014
DOI: 10.1371/journal.pone.0084311
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA Expression Signature of Bladder Cancer by Deep Sequencing: The Functional Significance of the miR-195/497 Cluster

Abstract: Current genome-wide microRNA (miRNA) expression signature analysis using deep sequencing technologies can drive the discovery of novel cancer pathways regulated by oncogenic and/or tumor suppressive miRNAs. We determined the genome-wide miRNA expression signature in bladder cancer (BC) by deep sequencing technology. A total of ten small RNA libraries were sequenced (five BCs and five samples of histologically normal bladder epithelia (NBE)), and 13,190,619 to 18,559,060 clean small RNA reads were obtained. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 50 publications
4
144
0
Order By: Relevance
“…Generally however, the myomiRs expressed in normal tissue are found downregulated in tumors when analysed by both qRTPCR and by sequencing platforms. Significantly, another deep sequencing profile of expressed miRs in bladder cancer [128] revealed a different myomiR expression profile to the above deep sequencing study [127] , yet confirmed the pattern of myomiR expression detected previously by the same group using microarray and qRTPCR techniques [93] ( Table 3). Overall, these various platform comparisons suggest the need to reevaluate the genomewide miR expression profiles of different cancers by use of deep sequencing and then to confirm findings using independent molecular methods.…”
Section: Cancer and Downregulated Myomirssupporting
confidence: 86%
See 1 more Smart Citation
“…Generally however, the myomiRs expressed in normal tissue are found downregulated in tumors when analysed by both qRTPCR and by sequencing platforms. Significantly, another deep sequencing profile of expressed miRs in bladder cancer [128] revealed a different myomiR expression profile to the above deep sequencing study [127] , yet confirmed the pattern of myomiR expression detected previously by the same group using microarray and qRTPCR techniques [93] ( Table 3). Overall, these various platform comparisons suggest the need to reevaluate the genomewide miR expression profiles of different cancers by use of deep sequencing and then to confirm findings using independent molecular methods.…”
Section: Cancer and Downregulated Myomirssupporting
confidence: 86%
“…Several large cohort studies have examined the changes in expressed miR networks in a variety of cancers. Navon et al [95] , Hart et al [125] , Han et al [127] , Itesako et al [128] and Volinia et al [145] noted that the downregulated expression of the miR-133/-1/-206 genes is associated with a variety of solid tissue cancers, with numerous other miRs also having highly significant oncogenic roles in particular cancer types. In sum, the downregulation of the various myomiRs contributes significantly to the upregulation of oncogenic proteins linked to regulation of cell cycle progression in solid tumors, sarcomas and carcinomas.…”
Section: Other Pleiotropic Pathwaysmentioning
confidence: 99%
“…For example, it is upregulated in metastatic melanoma (10) and some cases of lung cancer (16), and hepatocellular carcinoma (17). By contrast, it is preferentially downregulated in breast cancer (18), gastric cancer (17,19), colorectal cancer (20)(21)(22), and bladder cancer (23,24). However, inconsistent and inconclusive results have been reported concerning the expression and function of miR-195 in PCa (17,25).…”
Section: Discussionmentioning
confidence: 99%
“…41 It was observed that downregulation of miR-195 and miR-497 is related to bladder cancer progression and metastasis. 42 In a bladder cancer animal model study, it was observed that miR-582 delivery was connected with the inhibition of tumor growth and metastasis. 43 …”
Section: -9mentioning
confidence: 99%